Age differences in default mode activity on easy and difficult spatial judgment tasks - Park, Denise C.; Polk, Thad A.; Hebrank, Andrew C.; Jenkins, Lucas (Frontiers in Human Neuroscience, 2010)
The default network is a system of brain areas that are engaged when the mind is not involved in goal-directed activity. Most previous studies of age-related changes in default mode processing have used verbal tasks. We studied non-verbal spatial tasks that vary in difficulty. We presented old and young participants with two spatial judgment tasks: an easy categorical judgment and a more demanding coordinate judgment. We report that (a) Older adults show markedly less default network modulation than young on the demanding spatial task, but there is age equivalence on the easy task; (b) This Age x Task interaction is restricted to the default network: Brain areas that are deactivated by the tasks, but that are outside the default network, show no interaction; (c) Young adults exhibit significantly stronger functional connectivity among posterior regions of the default network compared with older adults, whereas older adults exhibit stronger connectivity between medial prefrontal cortex and other sites; and (d) The relationship of default activity to reaction time performance on the spatial tasks is mediated by age: in old adults, those who deactivate the default network most also perform best, whereas the opposite is true in younger adults. These results extend the findings of age-related changes in default mode processing and connectivity to visuo-spatial tasks and demonstrate that the results are specific to the default network.